Not all sectors are equal: LQ and DLQ Reveal Pangkalpinang’s true economic driver - Michael Kusuma; Brigitha Mega Rebeca (Faculty of Islamic Economics and Business UIN Salatiga, 2025)
Economic policy in Pangkalpinang City risks misallocation if relying solely on static data. This research identifies leading sectors (2018–2022) by integrating the Location Quotient (LQ) and Dynamic Location Quotient (DLQ). The study's novelty lies in using LQ to identify the current base and DLQ to project future potential, yielding a strategic map to differentiate between leading and mature sectors. Using time-series Gross Regional Domestic Product (GRDP) data from BPS, this research assesses each sector's specialization and dynamics. The results reveal a critical divergence: although 13 sectors were identified as base (LQ > 1), the analysis shows the information and communication sector is the only true leading sector (base and prospective). Other main base sectors, such as trade and construction, were found to be mature (base but non-prospective). This finding offers a practical implication: policy priorities must focus on accelerating the digital economy while maintaining stability in mature sectors.